2019
DOI: 10.1111/ijd.14688
|View full text |Cite
|
Sign up to set email alerts
|

IgG from atopic dermatitis patients induces non‐atopic infant thymic invariant natural killer T (iNKT) cells to produce IL‐4, IL‐17, and IL‐10

Abstract: Background Atopic dermatitis (AD) pathogenesis still needs to be elucidated, but invariant natural killer T (iNKT) cell involvement was already described by several groups. Our group has demonstrated that IgG antibodies purified from AD patients can modulate cytokine production by thymic T cells. Here we aimed to investigate if IgG from AD patients can modulate infant non-atopic thymic iNKT cells cytokine production in order to collaborate with the elucidation of AD development in infancy.Methods Thymic tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Extensive literature evidence demonstrates that the immune status of IgG donors may be related to differential modulation of thymic lymphocytes [ 26 , 31 , 45 , 46 ], which has been discussed in the literature since 2014 [ 6 , 47 ]. Among related observations, nonatopic IgG may be related to thymic maturation of lymphocytes with an allergy inhibition-related cytokine profile induced by γδT cells [ 48 ] as well as T CD4+ and CD8+ cells [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature evidence demonstrates that the immune status of IgG donors may be related to differential modulation of thymic lymphocytes [ 26 , 31 , 45 , 46 ], which has been discussed in the literature since 2014 [ 6 , 47 ]. Among related observations, nonatopic IgG may be related to thymic maturation of lymphocytes with an allergy inhibition-related cytokine profile induced by γδT cells [ 48 ] as well as T CD4+ and CD8+ cells [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the following years, it was also demonstrated that the IgG repertoire in patients who develop atopic dermatitis also modulates nonatopic human infant intrathymic abT and invariant natural killer T cells to produce a proinflammatory profile without influencing the proportions or viability of these cells. 89,90 This result suggests that IgG also influences the maturation of intrathymic abT and cells without causing cell depletion and making these cells more prone to inducing inflammatory disease.…”
Section: The Path To a New Hypothesismentioning
confidence: 95%
“…However, considering some breakthrough works in the literature demonstrating the differential effects of IgG repertoires on γδ T, αβ T, and B cells, we can observe a common characteristic that yields some additional speculation about this mechanism. The main described functional effects of IgG repertoires were obtained from chronic pathophysiological conditions including allergies [ 92 , 93 , 95 , 96 ], atopic dermatitis [ 94 , 97 ], or HIV-1-infected patients [ 111 ]. Considering those observations, we suggest that the γδTCR/IgG affinity determination results form a complex, long-term, and not yet clarified, process.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study has also demonstrated that IgG can modulate the production of IFN-γ and IL-10 by human thymic γδ T according to the donor’s immune status [ 93 ]. Corroborating this hypothesis, similar studies evaluating the potential of IgG molecules as mediators of modulatory effects on lymphocytes during their maturation have demonstrated several effects on human TCD4, TCD8, iNKT, and B cells [ 94 , 95 , 96 , 97 , 98 ].…”
Section: Evidenced and Proposed γδTcr Ligandsmentioning
confidence: 93%